The Detection of the Negative Effects of Interictal Epileptiform Discharges on Cognition: An Event-Related Potential Study. Issue 3 (March 2019) - Sun, Lihua; Zheng, Xiangyu; Liu, Chang; Shi, Mingchao; Lv, Yudan
Abstract : Abstract: Evidence from a neuropsychological test revealed that interictal epileptiform discharges (IEDs) may have significant impact on cognitive performance. Sometimes, neuropsychological tests may not be sensitive to detection of mild cognitive changes. We applied P300 and mismatch negativity (MMN) to detect mild cognitive changes caused by small amount of IEDs. Sixty-seven adult epilepsy patients and participants were divided into six groups according to different IEDs index. The patients with IED index greater than 7.5% showed longer latency and lower amplitude in the test of P300 and MMN than patients with IED index less than 7.5%, which indicated mild impaired cognitive function. The negative effect of IED index greater than 10% on cognitive has been found by neuropsychological test, whereas the mild negative effect of IED index greater than 7.5% has only been found by P300 and MMN. So, P300 and MMN may be more sensitive than neuropsychological tests to detect mild cognitive impairment caused by IEDs.